2019
DOI: 10.16997/jdd.319
|View full text |Cite
|
Sign up to set email alerts
|

Building a Better Referendum: Linking Mini-Publics and Mass Publics in Popular Votes

Abstract: Popular votes and mini-publics are both increasingly implemented as elected officials seek to build legitimacy for decisions, although these democratic innovations suffer from their own democratic deficits. Popular votes often do not live up to deliberative ideals while mini-publics may be limited in their capacities for inclusion and decision-making. Pairing these two devices can improve deliberation in referendum campaigns, while tying mini-publics to a clear and inclusive process for decision-making. Empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…All of these factors, intertwined, influence adolescents' career planning and decision-making. The career planning process consists of the ongoing iterative process of understanding oneself, setting career goals, reviewing skills, and searching for appropriate career options (Mckay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors, intertwined, influence adolescents' career planning and decision-making. The career planning process consists of the ongoing iterative process of understanding oneself, setting career goals, reviewing skills, and searching for appropriate career options (Mckay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…alternative. Yet the foundations of an alternative approach can be found in a long dormant but now resurgent line of inquiry that seeks to understand how popular vote processes are integrated with other institutions in democratic systems and how these interactions contribute to, or undermine, the realization of democratic ideals (see e.g., Setälä 2006Setälä , 2011Parkinson 2009;Leemann 2015;Prato and Strulovici 2017;Cheneval and el-Wakil 2018a;McKay 2019). To date, however, there has been no explicit articulation of the underlying normative and conceptual presuppositions of this new approach, which we call the democratic systems approach (DSA).…”
Section: Introductionmentioning
confidence: 99%
“…Given the substantial costs associated with the organization of mini-publics, this raises the question whether mini-publics are good value-for-money. While the effect of a minipublic on legitimacy perceptions may be more limited (and conditional) compared with the effect of a referendum, there are other potential benefits that could make mini-publics valuable including increases in citizens' ability to make considered political judgments and, more generally, improvements in the quality of public debate (Landemore, 2018;McKay, 2020). Finally, we found that the legitimacy-enhancing effects of mini-publics and, to a lesser extent, referendums are driven by citizens with low political trust.…”
Section: Discussionmentioning
confidence: 99%